High-intensity Interval Training in the Boundaries of the Severe Domain: Effects on Sprint and Endurance Performance - Turnes, T.; de Aguiar, R. A.; de Oliveira Cruz, R. S.; Pereira, K.; Salvador, A. F.; Caputo, F. (International Journal of Sports Medicine, 2016)
In order to compare the effects of two 4-week interval training programs performed at the lower (Critical Power, CP) or at the higher (The highest intensity at which V˙O2max is attained, IHIGH) intensities of the severe exercise domain on sprint and endurance cycling performance, 21 recreationally trained cyclists performed the Wingate Anaerobic Test (WAnT) and a 250-kJ time trial. Accumulated oxygen deficit (AOD), surface electromyography (RMS), and blood lactate kinetics were measured during the WAnT. Subjects were assigned to 105% CP or IHIGH groups. During the WAnT, significantly greater improvements in peak (Mean ±95%CI) (5.7±2.3% vs. 0.2±2.2%), mean power output (MPO) (3.7±2.0% vs. 0.5±1.8%), and RMS (17.8±7.4% vs. −15.7±7.9%) were observed in the IHIGH group (P<0.05). Higher and lower AOD, respectively, at the start and during the second half of the WAnT were observed after IHIGH training. The changes in RMS and MPO induced by the training were significantly correlated (r=0.584). The 2 interventions induced improvements in the 250-kJ time trial. In conclusion, although the improvements in endurance performance were similar, training at IHIGH led to higher gains in WAnT performance than training at 105%CP.
Keywords: exercise intensity domains; aerobic exercise; anaerobic exercise; neuromuscular function; short-term adjustments